Análisis de los Alojamientos Universitarios Sugeridos por las Universidades Ubicadas en las Localidades de Teusaquillo, Barrios Unidos y Chapinero (2023)
Bogotá, being the capital of Colombia, is the ideal destination for those who want to study a degree in accredited universities and who, being from other cities, do not have that possibility easily. That is why, having a wide variety of higher education institutions in locations such as Barrios Unidos, Teusaquillo, and Chapinero, it generates an increase in people looking for accommodation close to the campuses of these universities. Therefore, it is important to know what types of accommodations and services are offered near these institutions, as each of them is part of the Ministry of National Education as Higher Education Institutions.